Nature-Positive Solutions initiative baseline evaluation survey report: Vietnam - Boukaka, Sedi Anne; Azzarri, Carlo; Davis, Kristin E.; De Falcis, Eleonora (International Food Policy Research Institute, 2024)
The report’s main objective is to describe socio-economic conditions and agricultural systems in the survey areas. It provides a baseline assessment characterizing the main agricultural and socioeconomic challenges within the surveyed localities, and to inform the array of research interventions currently underway. Furthermore, the study will provide a baseline for estimating the impacts of NATURE+ (including waste management, water management, development or a resilient seed system, development of value chains for neglected and underutilized species, participatory varietal selection, encouragement of designs for increasing agrobiodiversity, etc.) on inclusion, poverty reduction, as well as on food security, livelihoods, and jobs. The report is structured as follows: Section 2 presents detailed information on the survey design, its coverage and implementation. Sections 3 and 4 discuss the main analytical results of the report, separately for the household and the workers survey, respectively. Finally, section 5 concludes.